SYMBOLIC COMMUNICATION OF CHILDREN WITH SPECIAL NEEDS IN SOCIAL INTERACTION AT SAKA KARAWANG NATURAL SCHOOL - Afifah, Zahra Nur; Kusmiati, Yopi (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This study aims to understand the forms of symbolic communication used by ABK during social interactions in the inclusive classroom environment of Sekolah Alam Karawang and involves the perspectives of teachers, parents, and non-ABK students regarding their understanding of the meaning of ABK symbolic communication. This study uses a qualitative research method, a phenomenological approach, a constructivist paradigm, and data collection through observation, documentation, data triangulation, and literature studies. The subjects in this study were Students with Special Needs (PDBK) with ADHD, slow learner, and deaf classifications; accompanying teachers; Regular Students (non-PDBK); and parents of students with special needs at Sekolah Alam Karawang. The object of the study was the social interaction of ABK with the environment at Sekolah Alam Karawang. As an analysis, this study uses the Symbolic Interactionism theory developed by G. H Mead and published by Herbert Blumer. The study's findings indicate that PDBK uses three forms of symbolic communication. First, body/physical movements are carried out by PDBK ADHD and slow learners. Second, repetition of words is done by one of the slow learners, PDBK and the deaf PDBK. Third, excessive use of emotions, done by the ADHD PDBK and one of the slow learner PDBK. Teachers, parents, and regular students (non-ABK) understand ABK symbolic communication differently. First, symbolic communication of body/physical movements is interpreted as encouragement, feelings of discomfort/nervousness/happiness, and unclear/strange children. Second, symbolic communication of repetition of words is interpreted as a form of difficulty in regulating thought patterns, a symbol of difficulty hearing, and a symbol of misunderstanding by student V and Mrs T. Third, symbolic communication of excessive use of emotions is interpreted as a form of channelling emotions/annoyance/wanting something and interpreting the form of communication using emotions as a form of anger and bad attitudes from ABK.